Analysis of the Influence of Subsidized Fertilizer Availability, Land Area Per Capita and Agricultural Labor on Rice Productivity in Madiun Regency - Arin refa deviana; M.Taufiq (LP2M IAIN Palopo, 2026)
This study aims to analyze the effects of subsidized fertilizer availability, land area per capita, and agricultural labor on rice productivity in Madiun Regency during the 2015–2024 period. The study employed a quantitative approach using secondary time-series data obtained from the Central Bureau of Statistics and related institutions. Data analysis was conducted using multiple linear regression with the assistance of EViews 12 software. Before estimating the regression model, classical assumption tests were carried out, including normality, autocorrelation, multicollinearity, and heteroscedasticity tests. The results indicate that partially, subsidized fertilizer and land area per capita do not have a significant effect on rice productivity. Meanwhile, agricultural labor has a significant negative effect on rice productivity. Simultaneously, all independent variables significantly affect rice productivity in Madiun Regency. The coefficient of determination value of 0.728532 indicates that 72.85% of the variation in rice productivity can be explained by subsidized fertilizer, land area per capita, and agricultural labor, while the remaining percentage is influenced by other factors outside the research model. These findings suggest that improving rice productivity cannot rely solely on the availability of production factors, but also requires more effective farm management, improved human resource quality, and the implementation of more efficient and appropriate agricultural technology.